Combinations of compound cold medicines should be used with caution: a case series - Jinlin Guo; Tianning Zhang; Shaohui Song; Junwei Li (Frontiers in Medicine)
BackgroundCompound cold medicines contain multiple ingredients and are widely used to alleviate discomfort caused by viral infections. It is generally believed that compound cold medicines rarely cause serious adverse reactions; therefore, patients do not need a prescription for them. Many individuals suffer from chronic illnesses and must take medications for prolonged periods. These patients may experience serious drug–drug interactions if they self-administer compound cold medicines. Here, we report three cases of severe adverse drug reactions induced by compound cold medicines.Case presentationAll patients had a chronic disease and had been taking medication for a long time without experiencing serious adverse reactions. However, after self-administering a compound cold medicine, serious drug–drug interactions occurred. In Case 1, a 67-year-old woman with no history of coronary artery disease or angina developed angina after concurrently taking diltiazem and compound methoxyphenamine. In Case 2, a 65-year-old man who was taking propylthiouracil for a year without any adverse reactions experienced mental status abnormalities and acute liver failure after taking “CONTAC NT.” In Case 3, a 63-year-old man, who was taking levodopa, entacapone, and selegiline for a long time, without any apparent adverse reactions, developed serotonin syndrome after adding CONTAC NT. These issues were resolved after the discontinuation of medication.ConclusionPatients should consult a pharmacist or physician before using compound cold medicines to avoid the risk of adverse reactions caused by drug–drug interactions.